STRATEGIES FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY IN SUPPORTING ENVIRONMENTAL SUSTAINABILITY: A THEORETICAL STUDY - Amândio de Araújo Sarmento (CV. Adiba Aisha Amira, 2024)
This theoretical review of Corporate Social Responsibility (CSR) implementation strategies in support of environmental sustainability highlights the importance of CSR integration into a company's business strategy, stakeholder engagement, and government policy support. The study emphasises that by making social and environmental responsibility an integral part of a company's vision and mission, as well as involving stakeholders in the process of planning and implementing environmentally friendly initiatives, the effectiveness of CSR programmes can be increased. In addition, supportive policies and regulations from the government will create a conducive environment for companies to implement sustainable practices. The synergy of these various elements is expected to strengthen the role of CSR in environmental conservation in an effective and sustainable manner.